-96-2x=24-12x

Simple and best practice solution for -96-2x=24-12x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -96-2x=24-12x equation:


Simplifying
-96 + -2x = 24 + -12x

Solving
-96 + -2x = 24 + -12x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '12x' to each side of the equation.
-96 + -2x + 12x = 24 + -12x + 12x

Combine like terms: -2x + 12x = 10x
-96 + 10x = 24 + -12x + 12x

Combine like terms: -12x + 12x = 0
-96 + 10x = 24 + 0
-96 + 10x = 24

Add '96' to each side of the equation.
-96 + 96 + 10x = 24 + 96

Combine like terms: -96 + 96 = 0
0 + 10x = 24 + 96
10x = 24 + 96

Combine like terms: 24 + 96 = 120
10x = 120

Divide each side by '10'.
x = 12

Simplifying
x = 12

See similar equations:

| 0.5x+0.6(2x+1)=5.7 | | 25-x=y | | 5x-4y-10z=-100 | | -x-133=9x+47 | | 2x-10=x-11 | | 132x^2-23x-132=0 | | 3x+12-2=-8 | | -3x-17=-6x+34 | | 7y=31-3x | | 5x+5=7x+12 | | 44+x-3+2x+1=180 | | 4(-m-7n)= | | 9x-55=110+2x | | -1+3x=9+-2x | | 6x+2=5(x-5)+7 | | 1/5(x-2)-(2x-3)=2/3(4x+1)-1/6(2x+7) | | 6x-26=12+4x | | 1-7y=3-8y | | 72+80+106+4x=360 | | 4x+8=-3x-20 | | -102-10x=-2x+138 | | 6p+9=5p+17 | | Y=2(0)-9 | | -7x-11=9x+25 | | 3(2r-2)=30 | | 3x-63=45+12x | | 28=4y^2 | | 4x=x+95 | | 5-4y=2-5y | | 5y-1+2y=3 | | -46-12x=-9x+41 | | Y=17-0.5(10.5) |

Equations solver categories